(untitled) (The Pakistan Development Review, 2018)
This paper compares the productivity and other characteristics of vertically integrated and non-integrated firms to investigate whether efficiency gains associated with a given liberalisation episode vary across firms, depending on their organisation. A theoretical setting of vertical integration in the textile and clothing industry is developed, to reveal that trade expansion triggers a change in the relative factor cost of these two types of firms, and consequently, a change in product range produced by them. The results are further backed by using a sample of clothing firms in Pakistan for the years 1992-2010 to analyse the effect of the phasing out of U.S. textile and clothing quotas on firm-level efficiency. The empirical findings illustrate that an increase in the level of quotas brings about a significant growth in the mean productivity of vertically integrated clothing firms. The diminishing efficiency of non-integrated firms points to the lack of ability of these firms to benefit from tighter quality control, timely revision of production policies and guarantee of supplies. JEL Classification: F13, F14, D24, L23 Keywords: Trade Liberalisation, Productivity, Vertical Integration, Firm Heterogeneity, Multi-Fibre Arrangement